2021
DOI: 10.1186/s43093-021-00095-4
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and economic growth in Nigeria

Abstract: The study empirically examines the nexus between human capital and economic growth in Nigeria between 1981 and 2017. This is predated by poor policy impact across the key sectors of the economy, such as education and health that would have transformed productivity to economic in Nigeria. In order to address this ugly happening, the study therefore employed vector autoregressive and Johansen techniques. The results disclosed that the estimated coefficients of human capital have long-run significant impact on ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…It was found that there is a significant positive evidence of spatial spillover effects of higher education and technological innovation on industrial structure upgrades when using the spatial Dubin model and the paper is occupied in learning the spatial effects of higher education and technological innovation. Nigerian human capital and economic growth nexus in between 1981 and 2017 are empirically examined in the study of Keji ( 2021 ). The cause is poor policy impact across the key sectors of the economy, such as education and health, which would have transformed productivity into economic growth in Nigeria.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that there is a significant positive evidence of spatial spillover effects of higher education and technological innovation on industrial structure upgrades when using the spatial Dubin model and the paper is occupied in learning the spatial effects of higher education and technological innovation. Nigerian human capital and economic growth nexus in between 1981 and 2017 are empirically examined in the study of Keji ( 2021 ). The cause is poor policy impact across the key sectors of the economy, such as education and health, which would have transformed productivity into economic growth in Nigeria.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…In order to achieve higher economic growth, institutional quality differences can be explained by the mixed evidence on the human capital–growth relationship, and the findings suggest that better governance contributes to the productive use of human capital. According to Keji ( 2021 ), economic growth in Nigeria is correlated with human capital between 1981 and 2017. Keji used vector autoregressive and Johansen techniques to analyze the relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality and human resources would imply more specialization in manufacturing activities than in primary activities within the value chains as well engaging in capital intensive production, especially when skilled labor and capital complement each other in the production process [61,62]. Keji [63] shows that a country's level of human capital is positively related to economic growth. In this sense, economic upgrading among EAC member states will be possible if the people with the necessary skills and experience are there.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…From the perspective of Nigeria, Keji (2021) constructed the nexus between human/physical capital and economic development. The study employed the VAR, VECM, and LM tests to measure the short-run/long-run relationship by considering the data set from 1981 to 2017 and predicted a significant and positive relationship between human/physical capital and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%